Economic and technical issues in the assessment of the regulatory WACC for utilities - Alberto Dell'Acqua (Bocconi University, Centre for Research on Geography, Resources, Environment, Energy and Networks (GREEN), 2021)
In this discussion paper I review and discuss the main economic and technical issues affecting the Regulatory WACC assessment in the sector of regulated utilities. I focus on three main compelling issues (the estimation of the risk-free rate, the treatment of risky debt, the calculation of the equity risk premium), for which I analyse the proposed approach of the Italian Regulatory Authority for Energy, Networks and Environment (ARERA) and some alternative viewpoints that can fulfil the current debate. Moreover, I also analyse some minor technical issues relating the consideration of a small size risk premium in the cost of capital estimation and the optimal investment level.
Keywords: 330; Versorgungswirtschaft; Energiewirtschaft; Regulierung; Kapitalkosten; Italien